2015
DOI: 10.1097/nrl.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts Between Patients With Lewy Body Dementia Syndromes and APOE-ε3/ε3 Patients With Late-onset Alzheimer Disease Dementia

Abstract: Functional performance, visuospatial skills, and behavioral symptoms are helpful for differential diagnoses between LBD and AD. Cerebrovascular risk might be more important for AD pathogenesis, whereas environmental factors might impact development of LBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…6,28 The incidence of delusions and hallucinations tends to be dissociated, considering that in AD delusions are usually more common than hallucinations, while in Lewy body dementia syndromes, hallucinations are more common than delusions. 31 Though APOE-e4 carrier status seems to predispose to late-onset depression, 3 particularly in women, 32 we did not find correlations with dysphoria in our sample. Nevertheless, one study showed that women have earlier AD onset when they are APOE-e4 carriers with a history of depression, 33 confirming that gender differences might affect dementia onset.…”
Section: 019mentioning
confidence: 49%
“…6,28 The incidence of delusions and hallucinations tends to be dissociated, considering that in AD delusions are usually more common than hallucinations, while in Lewy body dementia syndromes, hallucinations are more common than delusions. 31 Though APOE-e4 carrier status seems to predispose to late-onset depression, 3 particularly in women, 32 we did not find correlations with dysphoria in our sample. Nevertheless, one study showed that women have earlier AD onset when they are APOE-e4 carriers with a history of depression, 33 confirming that gender differences might affect dementia onset.…”
Section: 019mentioning
confidence: 49%
“…Future revisions could consider research findings and features described by investigators in other parts of the world. 49,50 The LBD- Findings from this study will be helpful in providing the initial evidence base for the use of the LBD-MOD in clinical research. The LBD-MOD appears to provide sufficient clinical discrimination between DLB and AD so that it can aid in diverse clinical research programs such as case-ascertainment in epidemiological studies, biomarker studies, cross-sectional and longitudinal studies, and clinicopathological correlation.…”
Section: Discussionmentioning
confidence: 97%
“…The LBD‐MOD was created by dementia and movement disorder experts from the United States. Future revisions could consider research findings and features described by investigators in other parts of the world 49,50 . The LBD‐MOD was validated in the context of an academic research setting where the prevalence of MCI and dementia in general, and DLB in particular, are high, and the participants tend to be highly educated and predominantly White.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DLB present with not only cognitive impairment as do patients with ADD, but also various symptoms such as Parkinsonism, visual hallucinations, REM sleep behavioral disorder (RBD), cognitive fluctuation, and depressive mood from early stages onwards (1). Therefore, various factors contribute to deficits in activities of daily living (ADL) (2), and family caregivers experience a high burden (3)(4)(5) in cases of patients with DLB rather than those with ADD, although there is a report that shows no difference in caregiver burden between DLB and ADD (6).…”
Section: Introductionmentioning
confidence: 99%